2018
DOI: 10.5812/hmj.86504
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Antioxidant Properties of Polygonatum orientale Desf and Tilia dasystyla Extracts by Different Methods and Solvents

Abstract: Background: Free radicals cause many diseases in humans. Antioxidants reduce the risk of cardiovascular disease and stroke by neutralizing free radicals and on the other hand, prevent the progression of cancer. The natural antioxidant enhances the antioxidant properties of plasma to prevent diseases such as heart disease, cancer, and stroke. Secondary metabolites derived from plants have a strong potential for antioxidant activity. Methods: The purpose of this study was to investigate the antioxidant activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Basil's strong action against free radicals can be attributed to the presence of these two substances. Basically, with the increase of total phenolic compounds, their antioxidant property also increases [23][24][25]. Hashemi et al [26] reported that the maximum amount of antioxidant activity in basil plant is under the effect of extract extraction by ultrasonic method and temperature of 45 degrees Celsius.…”
Section: Resultsmentioning
confidence: 99%
“…Basil's strong action against free radicals can be attributed to the presence of these two substances. Basically, with the increase of total phenolic compounds, their antioxidant property also increases [23][24][25]. Hashemi et al [26] reported that the maximum amount of antioxidant activity in basil plant is under the effect of extract extraction by ultrasonic method and temperature of 45 degrees Celsius.…”
Section: Resultsmentioning
confidence: 99%
“…According to Hanachi et al (2018), first methanol extracts showed more antioxidant properties than water extracts of T. dasytyla and P. orientale Desf (25). Thus, there is a direct correlation between phenolic compounds and antioxidant properties in these two plants.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is a direct correlation between phenolic compounds and antioxidant properties in these two plants. Methanol solvent can extract more phenolic compounds and show more antioxidant properties in both plant species (25).…”
Section: Discussionmentioning
confidence: 99%
“…Absolute methanol as blank and a sample containing absolute methanol 2mL and 1ml DPPH was considered as control. The absorption of the samples was read in a 517 nm (UNICO spectrophotometer UV/Vis 2100), and the percentage of free radicals cleared (RSA%) was calculated (14,15).…”
Section: Evaluation Of Antioxidant Activity By Dpph Radicalmentioning
confidence: 99%